Fatty Acid Binding Proteins FABP9 and FABP10 Participate in Antibacterial Responses in Chinese Mitten Crab, Eriocheir sinensis - Cheng, Lin (Public Library of Science, 2013)

(untitled)
Invertebrates rely solely on the innate immune system for defense against pathogens and other stimuli. Fatty acid binding proteins (FABP), members of the lipid binding proteins superfamily, play a crucial role in fatty acid transport and lipid metabolism and are also involved in gene expression induced by fatty acids. In the vertebrate immune system, FABP is involved in inflammation regulated by fatty acids through its interaction with peroxidase proliferator activate receptors (PPARs). However, the immune functions of FABP in invertebrates are not well characterized. For this reason, we investigated the immune functionality of two fatty acid binding proteins, Es-FABP9 and Es-FABP10, following lipopolysaccharide (LPS) challenge in the Chinese mitten crab (Eriocheir sinensis). An obvious variation in the expression of Es-FABP9 and Es-FABP10 mRNA in E. sinensis was observed in hepatopancreas, gills, and hemocytes post-LPS challenge. Recombinant proteins rEs-FABP9 and rEs-FABP10 exhibited distinct bacterial binding activity and bacterial agglutination activity against Escherichia coli and Staphylococcus aureus. Furthermore, bacterial growth inhibition assays demonstrated that rEs-FABP9 responds positively to the growth inhibition of Vibrio parahaemolyticuss and S. aureus, while rEs-FABP10 responds positively to the growth inhibition of Aeromonas hydrophila and Bacillus subtilis. Coating of agarose beads with recombinant rEs-FABP9 and rEs-FABP10 dramatically enhanced encapsulation of the beads by crab hemocytes in vitro. In conclusion, the data presented here demonstrate the participation of these two lipid metabolism-related proteins in the innate immune system of E. sinensis.